A Qualitative Examination of the Experiences of Veterans Treatment Court Graduates in Allegheny County, Pennsylvania - McCall, Janice D. (International journal of offender therapy and comparative criminology, 2019)
U.S. Veterans treatment courts (VTCs) serve justice-involved Veterans with behavioral health and reintegration issues. However, there is paucity of efforts examining VTC participants' experiences and distinguishing the unique operations of VTCs. We summarize a descriptive history of a large VTC program in a major metropolitan area (Pittsburgh, Pennsylvania) and examine the experiences of this VTC's participants. We used content analysis to code VTC graduation proceeding transcripts with complementary content data from resources distributed by the presiding Judge to entering participants. From 2009 through 2016, 118 Veterans were graduated, averaging 9 to 12 months for completion for those with felony or non-felony charges, and blended monitoring with positive reinforcement within a three-stage program. From 62 VTC graduates across eight graduations, testimonies centered on gratitude toward the treatment team, treatment readiness, treatments received, and reintegration. As several theoretical frameworks on behavior change exist, opportunities remain to enhance the delivery of the VTC.